Peran Manajemen Sarana dan Prasarana dalam Menstimulasi Kreativitas Anak Usia Dini: The Role of Facilities and Infrastructure Management in Stimulating Early Childhood Creativity - Solatiyah Asriyani; Erni Munastiwi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Educational facilities and infrastructure are one indicator of the quality of an educational institution. However, in reality, many facilities and infrastructure are not properly managed and optimized. Therefore, it is necessary to understand and implement facilities and infrastructure management to help broaden insight into the role of facility and infrastructure management in optimizing the teaching and learning process and stimulating and optimizing aspects of development in students. This study aims to determine the role of management of PAUD facilities and infrastructure in stimulating children's creativity, which is an aspect that must be further developed in children. This study uses the SLR (Systematic Literature Review) method. This research collects data by documenting and reviewing articles that are relevant to this research. Then the researcher reviewed the 10 articles obtained from Google Scholar. The results of the discussion from this study are based on a literature review conducted where management of facilities and infrastructure is needed in learning activities, especially in stimulating early childhood creativity. Â  ABSTRAKÂ  Sarana dan prasarana pendidikan merupakan salah satu indikator mutu suatu lembaga pendidikan. Namun kenyataannya banyak sarana dan prasarana yang tidak dikelola dan dioptimalkan sebagaimana mestinya. Oleh sebab itu, perlunya pemahaman dan pengimplementasian mengenai manajemen sarana dan prasarana untuk membantu memperluas wawasan mengenai peran manajemen sarana dan prasarana dalam mengoptimalkan proses belajar mengajar dan menstimulasi serta mengoptimalkan aspek-aspek perkembangan pada peserta didik. Penelitian ini bertujuan untuk mengetahui peran manajemen sarana dan prasarana PAUD dalam menstimulasi kreativitas anak yang merupakan aspek yang harus dikembangkan lebih lanjut pada anak. Penelitian ini menggunakan metode SLR (Systematic Literature Review). Penelitian ini mengumpulkan data dengan cara mendokumentasi dan mengulas kembali artikel yang relevan dengan penelitian ini. Kemudian peneliti mereview 10 artikel yang didapatkan dari Google Scholar. Adapun hasil pembahasan dari penelitian ini adalah berdasarkan kajian literatur yang dilakukan bahwa manajemen sarana dan prasarana sangat diperlukan dalam kegiatan pembelajaran terutama dalam menstimulus kreativitas anak usia dini